2018
DOI: 10.3390/antibiotics7020044
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and Methods to Access Novel Antibiotics from Actinomycetes

Abstract: Actinomycetes have been proven to be an excellent source of secondary metabolites for more than half a century. Exhibiting various bioactivities, they provide valuable approved drugs in clinical use. Most microorganisms are still untapped in terms of their capacity to produce secondary metabolites, since only a small fraction can be cultured in the laboratory. Thus, improving cultivation techniques to extend the range of secondary metabolite producers accessible under laboratory conditions is an important firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 300 publications
(393 reference statements)
2
118
0
4
Order By: Relevance
“…Mirroring their wide structural variety, NRPs fulfil diverse biological functions, including defense against competing microorganisms or chemotaxis . Several strategies are commonly employed for the discovery of new NRPs from bacteria, including genome mining, bioactivity‐guided isolation, and metabolome‐mining approaches . All three strategies have proven fruitful with myxobacteria, which are well‐established producers of SMs whilst being less extensively screened compared to, for example, the actinobacteria .…”
Section: Figuresupporting
confidence: 83%
“…Mirroring their wide structural variety, NRPs fulfil diverse biological functions, including defense against competing microorganisms or chemotaxis . Several strategies are commonly employed for the discovery of new NRPs from bacteria, including genome mining, bioactivity‐guided isolation, and metabolome‐mining approaches . All three strategies have proven fruitful with myxobacteria, which are well‐established producers of SMs whilst being less extensively screened compared to, for example, the actinobacteria .…”
Section: Figuresupporting
confidence: 83%
“…Our bioprospecting activities have focused on the phylum Actinobacteria (sensu Goodfellow [3]), the rationale for which we have rehearsed previously: unparalleled size and diversity of the taxon, extensive global and environmental distribution, continued discovery of new taxonomic radiations, genomes rich in natural product biosynthetic gene clusters (NP-BGC) and notable ecological and economic value. Although members of the genus Streptomyces continue to be the richest source of new actinobacterial specialized metabolites, members of non-streptomycete genera as pointed out by Hug et al [4] increasingly are being Bull and Goodfellow, Microbiology 2019 shown to produce chemically unique natural products, a fact well-illustrated by our work with Verrucosispora [5], Dermacoccus [6] and Lentzea [7].…”
Section: Introductionmentioning
confidence: 60%
“…Genomic-guided identification of new drug targets such as protein-protein interactions also will stimulate natural product bioprospecting given the extent of such interactions in nature. Moreover, as Hug et al [4] point out if production scale cultivation of target organisms compromises the exploitation of a promising natural product, culture-independent strategies that include metagenomics and heterologous expression of BGCs provide exciting approaches for the discovery of novel natural products among biosynthetic dark matter, as does the prospect of coupling genome sequencing with synthetic biology [33,34].…”
Section: Why Bother With Natural Products?mentioning
confidence: 99%
“…Antibiotic discovery by conventional approach have the drawback of frequent rediscovery of known metabolites. Hence, focus has to be set on rare microorganisms to have a higher potential of novel metabolites [39, 40, 44]. As Actinobacteria are the well-known antibiotic producers and due to the difficulties of rare Actinobacteria isolation under normal laboratory conditions, metagenomic approach was set to systematically assess the Actinobacterial diversity with respect to the overall microbial structure from pond sediment.…”
Section: Introductionmentioning
confidence: 99%